A facile route to the synthesis of coated maghemite nanocomposites for hyperthermia applications - Ferk, Gregor (Acta chimica slovenica, 2012)
CM-dextran-covered maghemite particles for applications in magnetic hyperthermia treatments were synthesized and their physical, magnetic and morphological properties were examined. Magnetic fluids were prepared and their heating proper ies in an alternating magnetic field were studied. The results reveal that the particle size and the thickness of the carboxy-methyl-dextran (CM-dextran) coatings have a decisive influence on the heating properties: specific absorption rate (SAR). The majority of the magnetic dissipation comes from the Neel relaxation, while the Brown contribution is small. A thermal steady state at the selected temperature (42 °C) can be achieved using synthesized maghemite particles with proper particle morphology and by controlling the magnetic field intensity or the frequency.
Keywords: hipertermija; hyperthermia; magnetic nanoparticles; magnetic properties; magnetne lastnosti; magnetni nanodelci